1998
DOI: 10.1086/514592
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus‐6 Infection After Liver Transplantation

Abstract: A diagnosis of posttransplantation human herpesvirus-6 (HHV-6) infection was established for eight adult recipients among a liver transplantation patient population of 121. The diagnosis was based on serology and demonstration of HHV-6 specific antigens in liver biopsy specimens with use of monoclonal antibodies and immunoperoxidase staining. A significant graft dysfunction was recorded in association with serodiagnosis. HHV-6 early antigens, as well as HHV-6 variant B antigens, were detected retrospectively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
109
4
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 6 publications
1
109
4
1
Order By: Relevance
“…It has been suggested that HHV-6 might be involved in fever and liver dysfunction in transplant recipients, and about 30% of the recipients with HHV-6 reactivation demonstrated either fever or hepatitis at the time of viral reactivation. In addition, HHV-6 infection has been suggested to cause graft rejection 10,11,22 ; however, only 1 recipient with viral reactivation had graft rejection in this study. This study together with the results of previous studies suggests that the indirect effects of HHV-6 reactivation are more important in graft rejection than the direct effects.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…It has been suggested that HHV-6 might be involved in fever and liver dysfunction in transplant recipients, and about 30% of the recipients with HHV-6 reactivation demonstrated either fever or hepatitis at the time of viral reactivation. In addition, HHV-6 infection has been suggested to cause graft rejection 10,11,22 ; however, only 1 recipient with viral reactivation had graft rejection in this study. This study together with the results of previous studies suggests that the indirect effects of HHV-6 reactivation are more important in graft rejection than the direct effects.…”
Section: Discussioncontrasting
confidence: 56%
“…In addition to cytomegalovirus (CMV), a well-known pathogen in immunocompromised patients, it has been proposed that human herpesvirus 6 (HHV-6) is also an opportunistic pathogen in liver transplant recipients. 1,2 Many investigators have studied the clinical features of HHV-6 infection in liver transplant recipients, using viral isolation, [3][4][5][6][7][8][9] antigenemia assay, [10][11][12][13][14] serological analysis, 15,16 and molecular analysis such as real-time polymerase chain reaction (PCR). [17][18][19][20][21][22] Several clinical features, including fever, 5,6,8,10 encephalitis, 7,23 CMV disease, 15,17,18 fungal infection, 7 graft dysfunction, 10,11,22 and hepatitis C virus (HCV) recurrence 9,19 after transplantation, have been suggested as clinical manifestations due to HHV-6 infection.…”
mentioning
confidence: 99%
“…40 This point mutation leads to ineffective inactivation of activated protein C. 26,27 Tanyel et al 41 reported a 10-yearold girl heterozygous for factor V Leiden mutation who 17,18 Low D/R age ratio 19 Prolonged surgical time 19 Intimal dissection 12 Bile leak 7,12 Liver from a non-heart-beating donor 12 Positive cytotoxic antibody cross-match 20 Poor baseline recipient hepatic arterial blood flow 21 Pediatric transplant recipient [4][5][6] Technique of graft preservation 22 Immunologic imbalance 23 Increased hematocrit 24 Coagulation abnormalities [25][26][27][28] Infections 1,29,30 Multiple rejection episodes 31 Chronic rejection 13 Tobacco use 31 Blood group type-incompatible grafts [14][15][16] experienced 3 episodes of HAT after an OLT. However, Hirshfield et al 42 showed that factor V Leiden mutation in the donor liver is not a major risk factor for hepatic vessel thrombosis and subsequent graft loss after OLT.…”
Section: Coagulation Abnormalitiesmentioning
confidence: 99%
“…Infection with HHV-6 and -7 correlates with graft rejection rather than the development of HAT, 30 especially when there is a coinfection with CMV. 47,48 CMV infection is increasingly prevalent with age; thus, most of the adult population has been infected.…”
Section: Infectionsmentioning
confidence: 99%
“…8,19,20 EBV-associated PTLD appears to be most effectively treated by tapering of the doses of the immunosuppressive drugs used to prevent transplant organ rejection. 17,21 Because different viruses can give rise to similar organ pathologies, [22][23][24][25][26][27][28][29] selection of the appropriate therapeutic approach involves accurate diagnosis of disease etiology.…”
mentioning
confidence: 99%